Perancangan Model Ontologi Domain Tanaman Upakara Hutan Yadnya Monkey Forest PadangTegal - I Kadek Dwika Pradnyana,; I Putu Gede Hendra Suputra, (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2025)
Upakara, which is frequently constructed from a variety of materials and given with symbolic roles and profound religious philosophical connotations, is an essential tool in Balinese Hindu religious events. "Tanaman Upakara" refers to plants that are offered. The kinds of upakara plants and their ceremonial applications are likewise unknown to most Balinese Hindus. Additionally, traditional, unstructured data on upakara flora is still recorded in the Yadnya Forest of Monkey Forest Padangtegal, a conservation site. This study uses ontology technology to try to solve these problems. As a formal representation of knowledge, ontology can improve data management effectiveness and information system interoperability. The Methontology method was used to create the ontology model for the Upakara Plant domain in the Yadnya Forest of Monkey Forest PadangTegal. The developed ontology model includes 17 classes, 8 object properties, 2 data properties, and 282 individuals. Evaluation was performed using SPARQL queries to test the ontology's correctness and functionality.
Keywords: Ontology; Tanaman Upakara; Methontology; Monkey Forest; Protégé